2010
DOI: 10.1002/cmmi.394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the radiation dose in micro‐CT with optimization of the scan protocol

Abstract: The radiation dose of a standard micro-CT scan is relatively high and could influence the experimental outcome. We believe that the presented adaptation of the scan protocol allows for accurate imaging without the risk of interfering with the experimental outcome of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 23 publications
(22 reference statements)
4
76
0
Order By: Relevance
“…Moreover, significant doses (well into the centigray range) were obtained when the standard settings, that is, as set by the manufacturers, were used (Table 1). Fortunately, the average absorbed dose could be lowered at least 7-fold by altering the preset parameters as described-a dose that was comparable to earlier published work (7). Moreover, the radial dose distribution illustrated that the x-rays are significantly attenuated as they traverse the body of the mouse (or phantom), typically leading to a relatively higher dose to the skin than to the body or organs situated more centrally.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, significant doses (well into the centigray range) were obtained when the standard settings, that is, as set by the manufacturers, were used (Table 1). Fortunately, the average absorbed dose could be lowered at least 7-fold by altering the preset parameters as described-a dose that was comparable to earlier published work (7). Moreover, the radial dose distribution illustrated that the x-rays are significantly attenuated as they traverse the body of the mouse (or phantom), typically leading to a relatively higher dose to the skin than to the body or organs situated more centrally.…”
Section: Discussionsupporting
confidence: 69%
“…Notwithstanding, the impact high dose CT has on longitudinal experimental results remains controversial. Studies often report opposing findings from no effects regarding dose delivered to tumors during longitudinal studies to results indicating high doses can induce tumor inhibition [19,20,[34][35][36]. Using a Mediso nanoPET/CT scanner, we found that for both the air/water and the TEM phantoms, decreasing CT dose resulted in visual image quality degradation and high noise, but had a relatively minimal impact on HU quantification, while adversely increasing small animal absorbed dose.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, the impact of varying microCT parameters on microPET/CT data and preclinical research results is poorly defined and not fully understood. Furthermore, the significance of different microCT parameters on radiation exposure to small laboratory animals is scarcely described in the literature [20], in particular cumulative severity for longitudinal studies. Given that cumulative radiation doses can become increasingly toxic [21], accurate microCT absorbed dose measurements are essential when undertaking longitudinal preclinical research.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the geometry of the mouse, the requirement for deep sedation and, therefore, poor lung motility leading to atelectasis, this modality is not easily translated to murine models. Additionally, CT has the disadvantages of requiring long acquisitions and of exposing the animal to high doses of radiation, which could affect some research studies (22). MRI, on the other hand, is more sensitive for pulmonary metastases and can be used for longitudinal studies of tumor development and therapeutic response, without the confounding variable of ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%